CONGENITAL MALARIA - Shah, Sajid Ali; Ahmed, Zeeshan; Lodhi, Munir Akmal; Malik, Nazir Ahmed (Journal of Ayub Medical College Abbottabad, 2015)
Neonates with congenital malaria may present with non-specific signs and symptoms which may be mistaken for neonatal sepsis and inborn error of metabolism resulting in delay of diagnosis and significant mortality and morbidity. Here we present a unique case of 25 days old premature female baby who was diagnosed to have mixed malarial infection. Despite standard treatment the patient was not responding well and was also diagnosed to have congenital adrenal hyperplasia.